Analysis of financial literacy in Sabah: Micro and SME - Sarimah Surianshah; Ho, Chong Mun; Salmah Topimin (Universiti Malaysia Sabah press, 2024)
The Malaysian Department of Insolvency has reported a significant number of bankrupt individuals in Malaysia with one-third of them are youth. Youth are the future catalyst for economic growth which has shifted the attention of the government and policymakers for their development. This study exclusively aims to examine business socioeconomic factors of financial literacy among micro and SME youths in Sabah. A random sample of 301 respondents in Sabah were employed, who are directly and indirectly involved in businesses. Methodologically, we conducted a survey questionnaire and used multiple linear regression to examine the financial literacy model. A noteworthy finding of this study was that micro and SME individuals tend to have better financial literacy if they have at least one to two years of business experience. Specifically, high investment and insurance literacy are statistically in line for individuals in micro businesses aged more than 30 years old. On the other hand, youth involved in micro businesses tend to have better literacy in these aspects if and only if they are enrolled in the manufacturing industry. When the micro-enterprise individuals are analysed in terms of their business experiences, only those with two or less than two years of experience tend to perform better financial literacies. These explored business socioeconomic factors may help financial institutions in conducting initiatives strategically such as in the microfinance programs in producing more mico and SME players with better financial-literate skills.